Bantam microRNA is a negative regulator of the Drosophila decapentaplegic pathway. Issue 2 (3rd April 2018) - Kane, Nanci S.; Vora, Mehul; Padgett, Richard W.; Li, Ying
ABSTRACT: Decapentaplegic (Dpp), the Drosophila homolog of the vertebrate bone morphogenetic protein (BMP2/4), is crucial for patterning and growth in many developmental contexts. The Dpp pathway is regulated at many different levels to exquisitely control its activity. We show that bantam (ban ), a microRNA, modulates Dpp signaling activity. Over expression of ban decreases phosphorylated Mothers against decapentaplegic (Mad) levels and negatively affects Dpp pathway transcriptional target genes, while null mutant clones of ban upregulate the pathway. We provide evidence that dpp upregulates ban in the wing imaginal disc, and attenuation of Dpp signaling results in a reduction of ban expression, showing that they function in a feedback loop. Furthermore, we show that this feedback loop is important for maintaining anterior-posterior compartment boundary stability in the wing disc through regulation of optomotor blind ( omb ), a known target of the pathway. Our results support a model that ban functions with dpp in a negative feedback loop.